Legal Study of Legal Protection for Victims of Cyberbullying Crimes Based on Law Number 1 of 2024 Concerning the Second Amendment to Law Number 11 of 2008 Concerning Electronic Information and Transactions - Firmansyah, Firmansyah; Risdalina, Risdalina; Kumalasari M, Indra (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The purpose of this study is to find out and understand about Legal Protection related to cyberbullying crimes regulated in Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions and Obstacles in law enforcement against victims of cyberbullying. The type of research used is normative legal research. Using a qualitative approach. Discussion Results: 1. Legal Protection related to cyberbullying crimes is regulated in Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions. The use of this Law has been felt to be very appropriate by applying the legal principle of lex specialis derogate legi generali which means that special regulations can override more general rules. So that the appropriate use in cases of cyberbullying is the use of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions. This law specifically regulates crimes that are often committed by perpetrators of crimes in cyberspace. 2. Obstacles in law enforcement against victims of cyberbullying include: No police report by victims of cyberbullying crimes; and Lack of adequate facilities and infrastructure to uncover cyberbullying crimes.